Efficacy and safety of trastuzumab deruxtecan in the treatment of HER2-low/positive advanced breast cancer: a single-arm meta-analysis - Li, Zongyu; Guo, Shangwen; Xue, Haoyi; Li, Luying; Guo, Yuyuan; Duan, Sinuo; Zhu, He (Frontiers in Pharmacology, 2023)
Background: Clinical trials have shown that the use of trastuzumab deruxtecan (DS-8201) alone is expected to provide novel therapeutic options for HER2-low/positive patients. Nevertheless, there are some variations in the efficacy of trial results, with potential risks at the safety level. Most DS-8201 trials in HER2 advanced breast cancer (ABC) have been conducted in the form of small-sample nonrandomized controlled studies, resulting in a lack of validated indicators to evaluate the efficacy and safety of DS-8201. Thus, this meta-analysis aimed to pool the results of various trials of DS-8201 alone to explore the efficacy and safety of DS-8201 in patients with HER2-low/positive advanced breast cancer. Methods: Relevant studies were searched in 7 databases, including Embase, PubMed, Web of Science, Cochrane Library, CNKI, VIP database and WanFang data, to collect single-arm studies on DS-8201 for HER2-low/positive ABC. MINORS was adopted for quality assessment and STATA 16.0 for data analysis. Results: Ten studies involving 1,108 patients were included in this meta-analysis. As for the tumor response rate, the pooled ORR and DCR of all studies reached 57% (95% CI: 47-67%) and 92% (95% CI: 89-96%) respectively, and the pooled ORRs of the HER2-low expression group and the HER2-positive expression group were 46% (95% CI: 35-56%) and 64% (95% CI: 54-74%). Only the low expression group achieved median survival time, with a pooled median PFS and median OS of 9.24 (95% CI: 7.54-10.94) months and 23.87 (95% CI: 21.56-26.17) months, respectively. The most common treatment-related adverse events from DS-8201 were nausea (all grades: 62%; ≥ grade III: 5%), fatigue (all grade: 44%; ≥ grade III: 6%), and alopecia (all grades: 38%; ≥ grade III: 0.5%). Drug-related interstitial lung disease or pneumonitis occurred in 13% of the 1,108 patients, with only a 1% incidence of AE ≥ grade III. Conclusions: The present study suggests that DS-8201 is effective and safe in the treatment of ABC with low or positive HER2 expression, providing additional relevant information for its clinical application. However, further strengthening of the pairs is needed, as well as more clinical studies to support individualized treatment.